IS FRANCHISE A PROSPECTIVE BUSINESS? THE CASE OF LAUNDRY BUSINESS IN PALANGKA RAYA (The Indonesian Journal of Business Administration, 2021)
The importance of small and medium-sized enterprises in the Indonesian economy is shown by their role as the largest market player and their contribution to employment, gross domestic product (GDP), exports, and fixed capital or investment. Franchise is one of the world's most common business models, including Indonesia. According to the Indonesia Franchise and License Association (WALI), the franchise market sector increased by more than 3% in 2018, with an accumulated revenue of 150 trillion rupiahs. To evaluate the viability of the franchise agreement, a financial feasibility report is performed to ascertain the profitability of the project and the danger that could emerge during the business process. The financial feasibility analysis is carried out on the capital budgeting methodology by calculating the Net Present Value (NPV), the Internal Rate of Return (IRR), the Payback Period, and Profitability Index for investment decision-making. This study has shown that the project can be financed with a total investment of IDR 101.6 million. The project potentially resulting NPV at IDR 157.1 million rupiahs and IRR at 39.35 percent. Investments can be returned in fewer than two years after service with a profitability index of 2.55. Keywords: Franchise, Laundry, Capital Budgeting Technique, Investment, MSME.